Boko Haram and the Geopolitics of Forced Migration in Nigeria - Mukhtar, Sadiq; Che Rose, Rosniza Aznie; Lam, Kuok Choy; Ibrahim Bibi-Farouk, Amina Ummulkhair (Universiti Utara Malaysia Press, 2018)
Migration is currently perceived as an epitome of globalization and a measuring gauge of global geopolitical mobility. In recent years, Nigeria has been faced with a series of migratory crises such as insurgency and conflict, forcing large numbers of people to flee from their various residential origins to neighboring countries as refugees and asylum seekers or within their country as Internally Displaced Persons (IDPs). This study explores how geographical and political factors intersects to provide explanations on the types and causes of forced migration due to the Boko Haram insurgent activities in Nigeria. The research engages the use of content analysis to examine relevant secondary data on Boko Haram insurgent activities and the geopolitics of forced migration in Nigeria. It is reported that from the total number of 2.1 million forced migrants in Nigeria as of May 2017, 9.7% are refugees in neighboring countries while others are spatially distributed in different states around the country as internally displaced persons. Furthermore, it was revealed that more than 97% of the internally displaced persons migrated due to the Boko Haram insurgent activities from the northeastern part of the country. It concluded that the migratory crises in Nigeria is predominantly caused by the activities of the Boko Haram insurgent group that subsequently forced the people to flee their origin because of fear for their lives coupled with the risk of persecution and the destruction of properties.